Horizontal Gene Transfer and the Collapse of Bacterial Diversity under Antibiotic Stress - Ghannawi, Lujain; Atta, Safaa; Salman, Ghufran; Gharab, karam; Fadhil, Haidar; Ibrahim, Hanan; Amer, Mohammed (ASJ - Academic Science Journal, 2026)
Horizontal gene transfer (HGT) is a biological process that enables bacteria to exchange genetic material independently of cell division and plays a key role in the spread of antibiotic resistance (ABR). This review provides an overview of how antibiotic stress, particularly misuse and low-dose exposure, can enhance HGT and alter bacterial community diversity. Based on evidence from environmental, clinical, and agriculture studies, we highlight that antibiotic pressure can facilitate HGT through several mechanisms, including increased cell-to-cell contact, activation of stress response pathways, and the formation of biofilms that act as hotspots for genetic exchange. As HGT promotes the spread of resistance genes and improves bacterial survival under antibiotic pressure, gradually, resistant strains may become dominant within microbial communities, leading to a decline in bacterial diversity. Such loss of diversity may result in significant ecological consequences, including reduced efficiency of pollutant degradation and disruption of nitrogen cycling processes. Furthermore, emerging strategies aimed at limiting HGT under antibiotic pressure are discussed; particularly those that may help preserve microbial diversity, support ecosystem stability, and contribute to improved public health outcomes.